Judge's Argument in Deciding Value-Added Tax Dispute on Refund of Advance Payment in Indonesia - Suharsono, Agus; Prasetyoningsih, Nanik (MultiTech Publisher, 2024)
Value-added tax disputes dominate tax disputes in Indonesia, one of which is a dispute over input tax that does not meet formal requirements and does not correspond to actual reality.​ This doctrinal research uses regulatory, conceptual, historical, case, and interpretive approaches; the data analyzed are secondary, namely laws, court decisions, and literature studies, which are interpreted to make conclusions and recommendations. The results of the study show that in the input tax dispute over the advance payment returned by the tax authorities, the tax invoice cannot be taken into account because the transactions listed in the tax invoice do not correspond to reality. The opinion of the Tax Court Judge, which the Supreme Court confirmed, was that the tax invoice could be taken into account because, in substance, the taxpayer had already been charged Value Added Tax by the transaction counterparty. Article 5A paragraph (2) of the Value Added Tax Law already regulates the Value Added Tax mechanism for the provision of taxable services that are canceled but does not yet regulate the refund of advance payments for taxable services that have not been provided, for this reason, it is recommended that this be added.